Od „Jerozolimy Królestwa Polskiego” do miejsca pamięci - żydowski Lublin - Dubrowska, Małgorzata (Studia Europaea Gnesnensia, 2010)
Jews played a significant role in the development of Lublin. In the articles, the author recapitulates the most important pages in the history of Lublin Jewish community, as well as its spiritual and material contribution to the history of the city. Written testimonies, of which the author made ample use, turned out greatly helpful in restoring the image of the lost Jewish quarter